On Linear Cellular Automata - Kulikov, V. R.; Kytmanov, A. A.; Poroshin, A. O.; Timofeev, I. V.; Fedchenko, D. P. (Programming and computer software, 2024)
wolfram cellular automata are considered and their operation is demonstrated using an example of traffic flow simulation. For the class of one-dimensional elementary cellular automata, the concept of linearity is introduced in the language of Zhegalkin operators. An algorithm for finding linear Zhegalkin operators with multipliers of three variables is presented. The algorithm is implemented in Python.